(untitled) - Werner, Patricia K. (New York, 1997)
This text introduces, practices, and applies basic grammatical structures in everyday contexts. The conversational approach helps students use the grammar structures they are studying in real-life communication. Ideal for pre-beginning to beginning ESOL students.
Keywords: English language; Spoken english,Problems, exercises, etc